GEOGRAPHIC INFORMATION SYSTEMS FOR RURAL DEVELOPMENT PLANNING AND MANAGEMENT - Stojanovic, Zaklina; Manic, Emilija (Economics of Agriculture, 2011)
Application of Geographic Information System (GIS) allows spatial analysis and modelling support for quality management and overall development of rural areas. The European approach to rural development is essentially territorial. Serbia is still on the way of defning basic terms and managing principles for the rural areas. Although there is no operational application, a certain awareness of necessity for a GIS in rural development exists in Serbia. In this sense, the paper analyzes the structure of GIS and the relation to external elements as the assumptions for further system application.